Hypokalemia with Recurrent Flaccid Paralysis - Poornima Tadkal; Vishwanath Siddini; Kishore Babu; T Chakravarthy (Indian Journal of Kidney Diseases)
Acute flaccid paralysis is a condition which is attributable to many etiologies. When a patient presents with recurrent acute flaccid paralysis, hypokalemic or hyerkalemic periodic paralysis should be considered especially if similar symptoms are seen in other family members. We present one such case of a 16-year-old patient with a history of recurrent acute flaccid paralysis. Investigations showed severe hypokalemia and rapid improvement in muscle power on correction of the same. In view of multiple episodes of flaccid paralysis which reverted after potassium supplements, and family history of primary hypokalemic periodic paralysis, genetic testing was done, which showed heterozygous missense variant c. 2005C >G; p.Arg669Gly in exon 12 of SCN4A gene, known to cause Type 2 primary hypokalemic periodic paralysis. We emphasize the importance of clinical history elicitation, which in our case helped us to consider hypokalemic periodic paralysis and prevented unnecessary further investigations.